Dry Waste Classification Using Quadratic Support Vector Machine for Intelligent Waste Management System - Ahmad Fahim Naqib Ahmad Faisal; Jabbar Al-Fattah Yahaya (Malaysian Journal of Science and Advanced Technology, 2021)
There has been a serious increment in solid waste in the past decades due to rapid urbanization and industrialization. Therefore, it becomes a big issue and challenges which need to have a great concern, as accumulation of solid waste would result in environmental pollution. Recycling is a method which has been prominent in order to deal with the problems, as it is assumed to be economically and environmentally beneficial. It is important to have a wide number of intelligent waste management system and several methods to overcome this challenge. This journal explores the application of image processing techniques in recyclable variety type of dry waste. An automated vision-based recognition system is modelled on image analysis which involves image acquisition, feature extraction, and classification. In this study, an intelligent waste material classification system is proposed to extract features from each dry waste image. The Quadratic Support Vector Machine, Cubic Support Vector Machine, Fine K-Nearest Neighbor, and Weighted K-Nearest Neighbor were used to classify the waste into different type such as bottle, tin, crumble, and flat waste sample. A Quadratic Support Vector Machine (QSVM) classifier led to promising results with accuracy of training, 89.7%.